Assessment of type II diabetes risk in a border community: Villa Guillermina, Pedro Juan Caballero, 2023 (Revista Científica UCOM Scientia, 2025)
Type 2 diabetes mellitus is a growing public health concern worldwide and in Latin America, with significant effects on quality of life and health system performance. Early identification of risk factors in specific communities enables targeted preventive strategies and strengthens primary health care. This study aimed to assess the risk of type 2 diabetes mellitus in the Villa Guillermina community of Pedro Juan Caballero, Paraguay, in 2023. An observational, descriptive, cross-sectional study was conducted using the FINDRISC questionnaire, validated in Spanish by the International Diabetes Federation and the World Health Organization. The survey was carried out in November 2023 during a community diabetes prevention event with a sample of 89 individuals of both sexes and various ages. Patients with a prior diagnosis of diabetes mellitus and pregnant women were excluded. Most participants were male (69%) and younger than 45 years (77%). Sixty-five percent had a BMI
Keywords: Diabetes Mellitus, Type 2; Risk Factors; Health Risk Assessment; Primary Health Care; Paraguay